Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Kinerja Karyawan Studi Kasus Pada Hotel Radisson Bandar Lampung - Puspita Sari , Anggi; Puji, Kemala; Candra, Ade (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of work discipline and compensation on employee performance at Radisson Hotel Lampung amid industry pressures in 2025. The objective is to analyze the partial and simultaneous influence of both variables on performance. A quantitative causal survey was conducted using questionnaires distributed to 98 employees selected through census sampling. Data were analyzed using multiple linear regression with SPSS. The results indicate that work discipline and compensation have positive and significant effects on employee performance, with compensation showing a more dominant influence. The findings imply that integrating consistent discipline policies and strategic compensation systems enhances organizational performance sustainability.